Perbedaan Efektifitas Terapi Ultrasound Diathermy (USD) Dengan Low-Level Laser Therapy (LLLT) Terhadap Pengurangan Nyeri Pada Frozen Shoulder - Nur Fadlilah; Wiek Israwan; Amin Zakaria; Fransisca Xaveria Hargiani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: The purpose of this study was to compare ultrasound diathermy with low-level laser therapy in the reducing pain management of frozen shoulder.Methods: This study used a quantitative experimental quasi method with a two group pre-post test design. The study conducted in a RSUD Ibnu Sina Gresik. Ten patients with frozen shoulder with an age range of more than 40 years and pain scale with visual analogue scale (VAS) more than 6 were randomly assigned to ultrasound diathermy group or low-level laser therapy group. Study participant received five treatment sessions of ultrasound diathermy or low-level laser therapy over a period twice a week. Outcome measures were a score of VAS.Results: For the 10 study participants were 6 women and 4 men, there were no between-group differences at baseline in VAS. At the end of the interventions the group showed a reducing pain. Normality test with Shapiro-wilk test, the data obtained from the treatment group are normally distributed. The test result show that the t-count value of sig. 0,649>0,05 so there is no significant difference between ultrasound diathermy and low-level laser therapy in reducing frozen shoulder pain. Conclusion: Overall, treatment with ultrasound diathermy and low-level laser therapy has an effect on reducing pain in frozen shoulder patients at RSUD Ibnu Sina Gresik and there is no significant difference between ultrasound diathermy with low-level laser therapy.